The Utilization of Green Mussel Shell Waste for The Production of Hydroxyapatite Using Sol-Gel Method - Aninda Ikaputri; Moh Nur Fuadzi; Luluk Edahwati; Sutiyono Sutiyono (Fakultas Teknik Universitas Wahid Hasyim, 2024)
Hydroxyapatite is a type of ceramic biomaterial made up of calcium and phosphate, with a chemical formula of Ca10(PO4)6(OH)2. The Calcium used in this research was obtained from Green Mussel Shell Waste Precipitated Calcium Carbonate. The research was conducted using the sol-gel method to determine the optimal conditions for hydroxyapatite synthesis with the variable of H3PO4 solution at 0.1 M, 0.5 M, and 1 M. The result at the concentration of H3PO4 on 1 M turns out the optimal condition. The hydroxyapatite synthesis using the sol-gel method with a concentration of 1 M pH 12 phosphoric acid was successfully conducted and known as the optimal condition in this research. From the synthesis results, the characterization of hydroxyapatite synthesis shows there was a P-O bond at 995.27 cm-1 and an OH- bond at 3068.75 cm-1. The ratio of Ca/P calculated is 1.68 which is close to the standard ratio Ca/P of hydroxyapatite.